Growth and optical spectroscopy of KPb2Cl5 crystal containing Mn2+ - Jia, Guohua; Wang, H.; Wang, C.; Zhao, S.; Deng, D.; Huang, L.; Hua, Y.; Li, C.; Xu, S. (Elsevier B.V., 2011)
KPb2Cl5:Mn2+ crystal with sizes of centimeters has been successfully grown by a modified Bridgman method. The electronic spectra of Mn2+ in the title compound have been measured at different temperatures and compared, revealing that the red emission observed at 10 and 77 K in the spectral range from 500 to 800 nm, which vanishes at room temperature, is associated with the radiation from Pb2+ ions with adjacent defects whereas the orange-red emission in the spectral range from 530 to 680 nm can be undoubtedly attributed to the spin forbidden transition 4T1g (4G) ? 6A 1g(6S) of Mn2+. The electronic excitation spectra are interpreted in a strong crystal field scheme with the use of the Tanabe-Sugano diagram. Good agreement with the experimental spectroscopic data is obtained with the use of crystal field splitting parameter 10Dq = 7902 cm-1, Racah parameters B = 618 cm-1, and C = 3549 cm -1. © 2011 Elsevier B.V. All rights reserved.